Overlapping Phenotype of Cardiomyopathy in a Patient with Double Mutation: A Case Report - Sigita Glaveckaitė; Violeta Mikštienė; Eglė Preikšaitienė; Rimvydas Norvilas; Ramūnas Janavičius; Nomeda Rima Valevičienė (Cardiogenetics, 2021)
Hypertrophic cardiomyopathy and left ventricular noncompaction commonly occur as separate disorders with distinct clinical and pathoanatomical features. However, these cardiomyopathies may have a similar genetic origin with mutations encoding sarcomeric proteins. The described case report demonstrates an example in which phenotypic expression of both diseases occurred in the same patient, who has two different alterations; one of them is a likely pathogenic variant in the MYL3 gene (MIM#160790) and the second variant in the MYH6 gene (MIM#160710) of unknown significance so far. To better understand associations between specific genetic variants and phenotypical expression of these genetic alterations and to stratify patient risk and decide on the most appropriate treatment, a comprehensive multimodality imaging approach and experienced multidisciplinary cardiomyopathy team decisions are warranted. In the clinical routine, awareness of the existence of complex cardiomyopathy phenotypes should be paid more attention during echocardiographic examination and should encourage a broader use of cardiovascular magnetic resonance.